Occupational risks among healthcare professionals in the dressing care unit of the Lagune University Hospital Center for Mother and Child (CHU-MEL), Cotonou, Benin: an exploratory descriptive qualitative study. - Alex; Senker Ndimba Bob; Mukadi Bamuleka Daniel; Hinson Antoine; Kafinga Luzolo Emery (Student's Journal of Health Research Africa, 2026)
Background: Healthcare workers are exposed to biological, chemical, physical, ergonomic, mechanical, and psychosocial hazards. This study analyzed occupational risks among healthcare workers in the dressing care unit of the Lagune University Hospital Center for Mother and Child (CHU-MEL) in Cotonou, Benin. Methods: An exploratory descriptive qualitative study was conducted among five healthcare workers assigned to the dressing care unit, comprising three state-registered nurses and two nursing assistants. Data were collected between January 25 and February 25, 2025, through five individual semi-structured interviews, each lasting approximately 45 minutes, and five non-participant direct observation sessions, each lasting approximately 10 minutes. The interview guide was pretested in a healthcare facility in the Democratic Republic of the Congo. Results: Six categories of occupational risks were identified: biological, chemical, physicochemical, ergonomic, mechanical, and psychosocial risks. Biological risks included exposure to blood and other biological fluids, inconsistent application of standard precautions, handling of healthcare waste, and incomplete hepatitis B vaccination coverage. Chemical risks involved the handling and storage of disinfectants and bleach. Ergonomic risks included awkward postures, prolonged standing, and inadequate furniture. Psychosocial risks were associated with workload, staffing constraints, fatigue, and occupational stress. Biological and psychosocial risks had the highest criticality scores (12 each), followed by ergonomic risks (8), chemical and mechanical risks (6 each), and physicochemical risks (3). Conclusion: Healthcare workers in the dressing care unit of CHU-MEL are exposed to multiple occupational risks, with biological and psychosocial risks representing the highest priorities in the context of this study. Recommendation: Occupational health and safety measures should prioritize the consistent application of standard precautions, continuous access to appropriate personal protective equipment, hepatitis B vaccination, proper healthcare waste management, safe handling of chemical products, improved workplace ergonomics, adequate staffing and workload management, as well as the prevention of occupational stress and fatigue.